2005
DOI: 10.1200/jco.2005.00.406
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Gene Expression Profiling for Response Prediction of Rectal Adenocarcinomas to Preoperative Chemoradiotherapy

Abstract: Our results suggest that pretherapeutic gene expression profiling may assist in response prediction of rectal adenocarcinomas to preoperative chemoradiotherapy. The implementation of gene expression profiles for treatment stratification and clinical management of cancer patients requires validation in large, independent studies, which are now warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
259
1
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(278 citation statements)
references
References 53 publications
(76 reference statements)
6
259
1
10
Order By: Relevance
“…An accuracy rate of 95% in a subset of 7 poor responders and 12 good responders using LOOCV was detected, and furthermore, using a prediction model based on these 19 patients, an 85% accurate prediction was found in a testing set of 47 patients consisting of patients having intermediate or good pathological responses (TRG 1-3). This is comparable to what has been found for gene expression analysis (71,(99)(100)(101) as prediction accuracies of 81%, 83%, 87%, and 89% by use of subsets of discriminating genes between responders and poor responders as assessed by tumor regression grade (TRG) or T-level downstaging was observed. Multiplex kinase activity is, therefore, a promising new tool in predicting response to preoperative chemoradiotherapy in rectal cancer.…”
Section: Tyrosine Kinase Pamchip ® Array Technology For Prediction Ofsupporting
confidence: 70%
See 2 more Smart Citations
“…An accuracy rate of 95% in a subset of 7 poor responders and 12 good responders using LOOCV was detected, and furthermore, using a prediction model based on these 19 patients, an 85% accurate prediction was found in a testing set of 47 patients consisting of patients having intermediate or good pathological responses (TRG 1-3). This is comparable to what has been found for gene expression analysis (71,(99)(100)(101) as prediction accuracies of 81%, 83%, 87%, and 89% by use of subsets of discriminating genes between responders and poor responders as assessed by tumor regression grade (TRG) or T-level downstaging was observed. Multiplex kinase activity is, therefore, a promising new tool in predicting response to preoperative chemoradiotherapy in rectal cancer.…”
Section: Tyrosine Kinase Pamchip ® Array Technology For Prediction Ofsupporting
confidence: 70%
“…With LOOCV, one sample is left out and the remaining samples are used to build a classifier, which is then used to classify the left out sample. The fraction of samples that are classified correctly provides unbiased estimates of prediction error (71). Initially, all 8 poor responders were used in the training set, however, the single TRG 5 patient was classified as good responder, and to obtain a robust classifier we chose to exclude this sample from further analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged exposure to caffeine, starting from weaning or from 60 days of age significantly decreased lung metastases in the PyMT transgenic mouse by 55% and 31% respectively, while introduction of the DBA/2J genome by breeding suppressed metastases by 90% (Table 1). Work from other labs has demonstrated that gene expression patterns of the primary tumors are able to predict metastatic capacity and chemotherapeutic efficiency both in animal models and in clinical trials (16)(17)(18)(19). To identify genes that were transcriptionally responsive to caffeine treatment, and were differentially regulated as a consequence of hereditary variations, gene expression patterns of the genetically or chemically modified primary tumors were analyzed using Affymetrix microarray.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, microarray gene expression profiling was successfully used to predict complete responses to preoperative chemoradiotherapy with advanced-stage rectal cancer (Ghadimi et al, 2005;Kim et al, 2007). Epidermal growth factor receptor (EGFR), vascular endothelial growth factor (VEGF), the p53 tumour suppressor and key mediators of cell-cycle arrest (p21, p27) and apoptosis (Bcl-2, apoptosis protease-activating factor-1 (APAF-1)) are among the immunohistochemical protein markers currently of interest as potential predictors of pathologic response, prognosis and recurrence-free survival in rectal cancer following neoadjuvant therapy (Giralt et al, 2005(Giralt et al, , 2007Lopez-Crapez et al, 2005;Kim et al, 2006;Lin et al, 2006;Smith et al, 2006;Bertolini et al, 2007).…”
mentioning
confidence: 99%